TEACHERS’ IMPLEMENTATION AND PERCEPTION OF THE FEEDBACK SESSION IN ENGLISH LANGUAGE TEACHING - Indah Amaliah; Chairil Anwar Korompot; Nur Aeni; Nur Aeni (State University of Makassar, 2022)
The purpose of this study is to answer the following research questions: How do teachers implement feedback sessions and what are teachers' perceptions of feedback sessions in English language teaching. This study uses the qualitative-descriptive approach. The participants of this research are three English teacher at SMA Negeri 3 Barru. The research instrument in this study was the interview protocol. The results of this study indicate that each teacher has a different perception of the feedback session and how they implemented it. Based on the classroom observation, every teacher implemented the correct feedback, that are the feedback must be corrective, the feedback must be given in timely manner, the feedback must be specific and refer to certain criteria, and the feedback is given to students as a tool to develop qualities in themselves. Meanwhile, the results of the interviews showed that every teacher has a positive perception of the feedback sessions in English language teaching. Keywords— Feedback Session, Implementation, Perception.